ANALISIS KINERJA KEUANGAN UNIT PENGELOLA KEUANGAN PADA BADAN KESWADAYAAN MASYARAKAT ATAU LEMBAGA KESWADAYAAN MASYARAKAT DI KOTA MADIUN - Nurul Qodriyah; Soffia Pudji Estiasih (Jurnal Akuntansi dan Pajak, 2022)
In the current effort to alleviate poverty in Indonesia, the Kotaku program (City Without Slums) tries to play an active role in assisting the Government in dealing with this crisis. In implementing the program, Kotaku does not go directly to the community, but is assisted by the Community Self-Sufficiency Agency/Institution (BKM/LKM). Through the UPK (Financial Management Unit) institution in each BKM/LKM with the focus of its activities, namely revolving economic activities, the more pro-active in carrying out its revolving loan activities. The purpose of this study was to assess the financial performance of UPK in managing revolving loans by UPK BKM/LKM in Madiun City. The research method uses descriptive qualitative analysis, with data collection methods using interviews and documentation, with financial performance indicators that have been determined by the UPK, namely Cost Coverage (CCr), Return on Investment (ROI), Portfolio at Risk (PAR) and Loan at Risk. (LAR), if the results are declared feasible, then the UPK has the right to continue the revolving loan program. The results of this study indicate that the performance of the UPK is said to be feasible to continue the revolving loan program, this is indicated by the presence of a higher ratio value than the value of the financial performance indicators, although there are several indicators that show unsatisfactory results but there are still efforts from the UPK management to continue to take action, corrective actions to maintain the continuity of this revolving loan program so that it can continue.